(untitled) (Kronika Bydgoska, 2012)
The history of the Barristers’ Chamber in Bydgoszcz 1945-2010 written by Janusz Kutta is another publication, which concems the history of Bydgoszcz from different points of view. The book is of occasional character. It was inspired by the Bydgoszcz Bar, which decided this way to celebrate the 60"' anniversary of its existence and the operation of its own self-govemment. The book contains an analysis of facts documented with written sources. The book construction is of chronological-problem character. It is divided into 7 chapters, with subsections devoted to detailed issues. Individually discussed topics include legał foundations of the Chamber’s operation in the background of the generał political situation, structure of the authorities, statutory operation, political and social activity of barristers, and their role in the community. The basie course of reflections is completed with 3 finał comprehensive appendices, i.e. lists of barristers and legał interns, makeups of the Barristers’ Council in Bydgoszcz in the years 1945-2010, and selected documents. Text orientation is facilitated with a list of abbreviations, lists of tables, maps and illustrations, and a personal index. The book includes also summaries in German and English.